Panton–Valentine leukocidin-positive Staphylococcus aureus: a position statement from the International Society of Chemotherapy - Saeed, K.; Gould, I.; Espositio, S.; Ahmad-Saeed, N.; Ahmed, S.; Alp, E.; Bal, A.; Bassetti, M.; Bonnet, E.; Chan, M.; Coombs, Geoffrey; Dancer, S.; et al. (Elsevier Science, 2018)
Panton–Valentine leukocidin (PVL), a pore-forming cytotoxic secreted toxin, has been associated with severe Staphylococcus aureus pneumonia and prototypical skin lesions. The reported incidence and prevalence of PVL-positive S. aureus (PVLP-SA) varies globally and suffers from a selective reporting bias towards community-associated methicillin-resistant S. aureus (CA-MRSA). Recent studies, however, have identified PVL-positive methicillin-susceptible S. aureus (MSSA) more frequently than previously expected. In this review, a group of experts from four continents affiliated with the International Society of Chemotherapy (ISC) offer a position statement on the important aspects of PVL in S. aureus epidemiology, antimicrobial treatment and decolonisation, and aim to highlight future areas for collaboration and research.